The cultural landscape of megalithic tombs in Denmark, reconstructed by soil pollen analysis - Andersen, †Svend Th. (Danish Journal of Archaeology, 2012)
Forty-four pollen spectra from 25 megalithic tombs (5 dolmens and 20 passage graves) in eastern and northern Denmark reveal a highly varied landscape with remains of woodland, coppice woods or secondary woodland and open areas of grass and herb vegetation. Very often there are traces of tree burning. The dominant land-use was cereal growing on burnt sites and pasture. A long-fallow swidden rotation based on the burning of coppice, cereal growing, pasture and coppice regeneration is indicated.